Foreign Direct Investment - Its Success or Failure in India - Sharma, Ankit (Journal of Advanced Research in Economics and Business Management, 2021)
With the start of globalization, creating nations, especially those in Asia, have been seeing a gigantic surge of FDI inflows amid the past two decades. Indeed in spite of the fact that India has been a latecomer to the FDI scene compared to other East Asian nations, its impressive showcase potential and a liberalized arrangement administration has supported its fascination as a favorable goal for outside financial specialists. This article to look at the affect of FDI on the Indian economy, especially after two decades of financial changes, and analyzes the challenges to position itself favorably within the worldwide competition for FDI. The article provides the major approach suggestions from this examination, other than drawing consideration on the complexities in deciphering FDI information in India. Concurring to Division for Advancement of Industry and Inner Exchange (DPIIT), FDI value influx in India stood at US$ 500.12 billion between April 2000 and September 2020, demonstrating that Government’s exertion to move forward ease of doing trade and unwinding FDI standards has surrender comes about. How to cite this article: Sharma A. Foreign Direct Investment - Its Success or Failure In India. J Adv Res Eco Busi Mgmt 2021; 4(1): 17-21